A phase I, placebo-controlled, randomized, double-blind, single ascending dose-ranging study to evaluate the safety and tolerability of a novel biophysical bronchodilator (S-1226) administered by nebulization in healthy volunteers. Issue 1 (December 2016) - Green, Francis; Leigh, Richard; Fadayomi, Morenike; Lalli, Gurkeet; Chiu, Andrea; Shrestha, Grishma; ElShahat, Sharif; Nelson, David; El Mays, Tamer; Pieron, Cora; Dennis, John
Abstract Background A major challenge in treating acute asthma exacerbations is the need to open constricted airways rapidly enough to reestablish ventilation and allow delivery of conventional medication to diseased airways. The solution requires a new approach that considers both biophysical and pharmacological aspects of treatments used in acute asthma. The result of testing several formulations was S-1226: carbon dioxide-enriched air delivered in nebulized perflubron, a synthetic surfactant. These agents act synergistically to rapidly reopen closed airways within seconds. The bronchodilator effect is independent of β-adrenergic and cholinergic mediated-signaling pathways, offering a unique mechanism of action. S-1226 has a low toxicity profile and was effective in treating bronchoconstriction in animal models of asthma. The goal of the present study was to evaluate the safety and tolerability of S-1226 in healthy human subjects. Methods The phase I study was a single-center, randomized, double-blind, placebo-controlled, sequential, single-ascending-dose study conducted in Canada. Thirty-six subjects were distributed into three cohorts. Within each cohort, subjects were randomized to receive a single dose of S-1226 or a matching placebo administered over a 2-minute nebulization period. S-1226 was formulated with perflubron and 4 %, 8 %, or 12 % CO2 . The dose of CO2 was sequentially escalated by cohort. The safety and tolerability of S-1226 were evaluated through assessment of adverse events, vital signs, 12-lead electrocardiograms, clinical laboratory parameters, and physical examinations. Results S-1226 was safe and well tolerated at all three CO2 levels (4 %, 8 %, and 12 %). A total of 28 adverse events were reported, and all were judged mild in severity. Twenty-four adverse events occurred in the S-1226 cohort, of which five were considered remotely related and six possibly related to S-1226. Conclusions S-1226 is a novel drug being developed for the treatment of acute asthma exacerbations. It consists of CO2 -enriched air and perflubron and has potential to offer rapid and potent bronchodilation. The results of the study indicate that S-1226 is safe and well tolerated. All adverse events were mild, reversible, and likely due to known side effects of CO2 inhalation. Trial registration ClinicalTrials.govNCT02616770 . Registered on 25 November 2015.